Forecasting the cutting force in end milling - Petrakov, Yuri; Ohrimenko, Olexander; Gladskyi, Maksym (Eastern-European journal of enterprise technologies, 2024)
The object of this study is the process of end milling, taking into account the discontinuity of the process, simultaneous cutting with several flutes arranged in a spiral, tool runout, and feedback in the elastic machining system, in particular, for the depth of cutting. The subject of the study is the cutting force and identification of its empirical model. During identification, the cutting force coefficient is automatically determined when matching the theoretical and experimental oscillograms of the cutting force component. The reported results related to forecasting the cutting force at end milling are based on a mechanistic approach and involve the process modeling method for forecasting. The simulation uses an algorithm for representing the interaction of the cutter flutes workpiece engagement, based on the scan of the cutter according to the rotation angle coordinate. The algorithm makes it possible to identify empirical coefficients and exponents of the cutting force model based on experimental oscillograms of cutting force components. The built model is implemented in an application program and owing to the representation of the machining system in the form of a closed structural diagram, it allows predicting the elastic displacement, which will determine the actual cutting depth. The developed program under an interactive mode using digital files of experimental cutting force components makes it possible to perform model identification and predict cutting force components with an error of 4.6 %. The adequacy of the algorithms was confirmed by measuring the profile of the machined surface in the places where the cutting mode changed with the feed stopped. The developed simulation algorithm makes it possible to take into account the simultaneous cutting by several flutes arranged in a spiral, the runout of the tool, and the feedback in the elastic machining system, in particular, the depth of cutting Об’єктом дослідження є процес кінцевого фрезерування з урахуванням переривчастості процесу, одночасного різання декількома лезами, що розташовані за спіраллю, биття інструменту та зворотних зв’язків в пружній обробній системі, зокрема за глибиною різання. Предметом дослідження є сила різання та ідентифікація її емпіричної моделі. При ідентифікації автоматично визначається коефіцієнт сили різання при узгодження теоретичної та експериментальної осцилограм складової сили різання. Представлені результати прогнозування сили різання при кінцевому фрезеруванні, що базуються на механістичному підході і використовують для прогнозування метод моделювання процесу. Моделювання використовує алгоритм представлення взаємодії лез фрези з заготовкою, що ґрунтується на розгортці фрези за координатою кута повороту. Алгоритм дозволяє ідентифікувати емпіричні коефіцієнт і показники ступеня моделі сили різання за експериментальними осцилограмами складових сили різання. Створена модель втілена в прикладну програму і завдяки представленню обробної системи у вигляді замкненої структурної схеми дозволяє передбачувати пружний зсув, що визначатиме фактичну глибину різання. Створена програма в інтерактивному режимі з використанням цифрових файлів експериментальних складових сили різання дозволяє виконувати ідентифікацію моделі і прогнозувати складові сили різання з похибкою 4,6 %. Адекватність алгоритмів підтверджена вимірами профілю обробленої поверхні в місцях зміни режиму різання з зупинкою подачі. Розроблений алгоритм моделювання дозволяє ураховувати одночасне різання декількома лезами, що розташовані за спіраллю, биття інструменту та зворотні зв’язки в пружній обробній системі, зокрема за глибиною різання